Effects of solution treatment temperature on the mechanical properties of commercial recycled aluminium alloy cylinder head (A319) / Murizam Darus. - Murizam Darus (School of Materials Engineering, Universiti Malaysia Perlis, 2010)
The present work was performed to investigate the effect of different solution treatment temperature on commercial recycled aluminium alloy cylinder head during artificial ageing process.